Konsep Kebenaran, Relativisme dan Pluralisme Agama - Salamah Eka Susanti (HUMANISTIKA : Jurnal Keislaman, 2017)
Sociologically we are now in the environment of ethnic and religious Globalism and Pluralism, an anthropological social necessity that we must accept. This development in the order makes theologians, both from the Jewish, Christian and Islamic circles, reflect and review the concept of missionaryism and the concept of an eschatological eschatological monopoly beyond their own faith. “Is the path of God’s salvation simply monopolized by a religious tradition?”, That is one of the inevitable but often disturbing questions of one’s faith. Claiming the absolute truth of religion is not a solution to the problem of religious pluralism, but it is the source of the problem itself. The absolute truth claim of each religion does not come from “the Absolute”, but comes from the development of self-confessions of each religion in its enclosed territory, the claim of truth comes from the subjectivity of man, not the objectivity of the Divine. In the realm of religion, the question of pluralism arises because of the diversity of experience in translating the Saints (devine). Many religious philosophers claim that all claims of religious truth stem from claims to the nature of God, many of which are caused by our “not having a neutral premise” about Him. We all have perceptions about Him, and that’s what we think is right, so that’s different from what we think we’ll think wrong. This is the culprit of the religious truth claim battle. It should be accompanied by an awareness that the claim of religious truth is only local, inseparable in the context of a specific local-temporial context, not universal. While we rationally accept the fact that there is a plurality of religions and offers of eschatological eschatological paths, every religious person is always required to accept, acknowledge and believe that only his righteous path of salvation is true. In the absence of a firm belief and the attitude of obscuring the truth of his faith then one will be doubtful in his religious commands and may be himself less strong in his faith, or even judge himself as a half-hearted man in religion. Without a firm belief that his path the straight path that connects itself with God, then one is difficult to obtain spiritual and spiritual enlightenment.